Evaluation of cost and length of stay, linked to complications associated with major surgical procedures. Issue 1 (2nd January 2018) - Pirson, M.; Dehanne, F.; Van den Bulcke, J.; Leclercq, P.; Martins, D.; De Wever, A.
Abstract: Introduction: A lot of studies have demonstrated the possibility of reducing the number of post-operative complications in the domain of major surgical procedures with the use of medical preventive techniques. However, complications following surgical procedures are unfortunately frequent and are a major problem, not only because of the impact for the patient, but also because of economic consequences that they provoke. The aim of the present study is to evaluate the extra length of stay and the extra cost, born by the hospital and the social security, linked to complications, incurring after major surgical procedures. Material and methods: Study based on the data from 13 Belgian hospitals for the year 2012. Complications were extracted through medical discharge summaries. The cost born by the social security was assessed on the basis of the billing data, hospital cost are taken from cost accounting studies. Results: The rate of complication for all the hospitals is 6.6%. About 30.3% of inpatient stays having a major or extreme severity of index had a complication during the stay, 1.8% of stays with a minor or moderate severity of index had a complication. The extra length of stay is 19.38 days when the stay has had a complication ( p  < 0.001). The additional mean cost borne from the hospital perspective is €21 353.07 and €8 026.65 for the social security. This additional mean cost varies greatly from one hospital to another. Discussion/conclusion: The present study has shown that the actual financing do not cover real hospital costs in the field of major surgical procedures having caused complications. Results should encourage Belgian authorities to propose and finance preventive measures in order to reduce these complications, which represent major economic impacts, not only for authorities but also for hospitals.